Analysis of potential landslides and local wisdom approaches in dealing with them in the Naga Traditional Village Area, Tasikmalaya Regency - Marlyono Setio Galih; Mustofa Romy Faisal; Wahyu Firdaus Dede; Arini Chaerunnisa; Danawijaya Indra (E3S Web of Conferences)
Indonesia has a lot of natural resource wealth, but on the other hand, Indonesia has various threats or risks of natural disasters as a logical consequence of Indonesia’s geographical conditions. One of the disasters that often occurs in Indonesia is landslides. The West Java Province region, in this case Tasikmalaya Regency, which contains the Naga Traditional Village, has the potential for landslides because it has a hilly morphology. So, this research not only aims to analyze the potential for landslides in Kampung Naga, but also aims to analyze how to deal with landslides through the local wisdom of the Kampung Naga community. The method used is a scoring and weighting method using a Geographic Information System (GIS), which involves several thematic data, namely data on land use, rainfall, soil type, geology and slope in the research area, which is adjusted to the estimation model from Puslittanak. Then use the Qualitative Descriptive method to analyze the traditional wisdom or local wisdom of the community in dealing with landslide disasters. The research results show that based on the analysis, landslide potential falls into three categories, namely very low, low and medium. Then the traditional wisdom or local wisdom of the community in dealing with landslides is by making terraces which is called entep stone or umpak stone , with stones obtained from the Ciwulan River next to the village. Apart from that, the community also continues to protect the land cover on the hill by making it a prohibited forest (Leuweung Larangan) and a forest entrustment (Leuweung Titipan) , so that its use can be well controlled, and maintain the strength of the soil.